Implementasi Model Sains Teknologi Masyarakat (STM) terhadap Keterampilan Berpikir Kritis dan Merancang Eksperimen Sub Tema Hidroponik pada Materi Reproduksi Tanaman dan Hewan - Satriadi, Asep; Hindriana, Anna Fitri; Sulistyono, Sulistyono (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2021)
Learning proces is teacher more animal dominant than students so students inclined concept memorize withhout know how they found concep like behave the trees issue can’t grow without land. The purposes of this researchto increase critical thinking skill dan experiment stake out for junior high school (MTs). Students were though experiment science model society technology sub theme hidroponik to material trees and animals reproduction. This research ussed experimet methode with pre test- pos test design group. Research populate all of IX class junior high school (MTs) 1 Majalengka. The sample of this research was determined according to purposive random sampling endwise two classes. Experiment classes were given treatment to use science model society tecnology and control classes were given treetmen comunicative, discussiom and practice each 30 studeyd. the use of data collectives were multiple choice to criticals thinking skill, heading experiment was stake out and students questionnaire respons for implementasing science model society technology at experiment classes. For hipotesis resarch was test –t with two sample partner and helping software spss 26, result research be could : 1. Resembling scince model society technology 82%. 2. There are increase studnts critical thinking at experiment class can be average N- gain 0.49 with the biggest 0.99 and smallest 0.1 , whereas control class can be average N- gain 0.27 with teh biggest 0.5 and smallest 0,1 . So it can be concluded that the students use critical thinking skill to increase. 3. There are increase to avarage experiment stake out class more value, wheras 3.6, the average control class 2.83 then experiment stake out to increase though science model society tecnology. 4. Students response to science model society tecnology 96.5%. 5. There were corelative betwen critical thinking skill dan experiment stakeout with more value 0.597.